Developing an engaging and effective mascot design for promoting alternative energy source awareness - Kurniawati Homan, Devi; Sondang Silitonga, Nixie Carissa; Witabora, Jonata (Gelar: Jurnal Seni Budaya, 2023)
Alternative energy sources are one of the solutions that can help address the issues of the energy crisis and global climate change. Indonesia has joined other countries in pursuing the implementation of a net-zero emissions policy by 2050. Due to Indonesia's geographic location, which is situated across the equator, the country can benefit from the use of alternative solar energy. According to data from the Ministry of Energy and Mineral Resources, Indonesia's potential solar energy capacity can reach around 4.8 KWh/m2, equivalent to 112.000 GWp, but currently, only about 10MWp is being utilized. This number highlights the need for Indonesia to develop a strategic plan for harnessing its solar energy resources. Visual communication design can play a significant role in the success of this transition. One highly effective form of visual communication is the use of a mascot. A mascot serves as a storyteller; it is memorable and embodies the core values of what it represents. It is a powerful tool for conveying messages to the audience. The creation of this mascot aims to engage the masses in the adoption of alternative energy sources and plays a crucial role in appealing to the emotional aspect of the audience, influencing their decision-making process regarding energy sources. This research focuses on the creative process of designing the mascot's visual representation. Using a three-step design research approach, we have identified the visual elements necessary to develop the mascot's shape, form, color, and characteristics. The resulting mascot design symbolizes a brighter future for energy consumption. It's important to note that this research exclusively addresses the visual aspect of the mascot. Further studies are required to assess the mascot's effectiveness across different forms of media serving specific purposes.